Penerapan Sistem Informasi Manajemen Kepegawaian (SIMPEG) di Kementrian Hukum dan HAM Sumatera Utara - Putri Febrianti; Nurlaila Nurlaila (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out and examine the implementation of the Personnel Management Information System (SIMPEG) at the Ministry of Law and Human Rights of North Sumatra to realize E-Government. This research is a descriptive qualitative type with data collection techniques carried out through triangulation which includes interviews, observation and documentation studies, then the data is analyzed using the Miles and Huberman model where the data is reduced, presented and conclusions are drawn. The results of this research are that the application of SIMPEG has been implemented according to its function to develop electronic-based government administration in improving the quality of personnel services optimally, as well as as a medium for making personnel decisions. Efforts made to optimize the implementation of SIMPEG are to carry out routine monitoring of each individual's performance behavior by their direct superior, then there is integrated socialization as a form of support from internal and external sources by maximizing the potential of existing resources.